Green Practices on Bank’s Environmental Performance - Chhetri, Ashmita Dahal; Chhetri, Guna Raj (Journal of Economics and Management, 2024)
The study examines the adoption of green banking practices among commercial banks in Chitwan and its impact on environmental performance. The researcher aims to assess the green banking practices employed by commercial banks, examining the relationship between these practices and bank performance, and analyse the impact of green banking on the perceived performance of commercial banks. The study employs an analytical research design to analyze the variables associated with green banking practices. The population comprises bankers from financial institutions across Chitwan, with a sample of 189 respondents selected through purposive sampling. Statistical tools were used to analyze the relationships between independent variables (employee-related practices, daily operation practices, customer-related practices, and bank policy-related practices) and the dependent variable (bank's environmental performance). The results showed that commercial banks in Chitwan generally have a positive view of their sustainability practices, with bank policy-relatedpractices showing the highest positive perception among employees. The study also found a positive correlation between green banking practices and environmental performance, with bank policy-related practices having the strongest relationship and customer-related practices the weakest. The study underscores the importance ofstrategic policy implementation and employee involvement in promoting sustainability within the banking sector.